Bridging Material Science and Clinical Longevity: A Comprehensive Review of Properties, Selection, and Translational Relevance of Contemporary Dental Restorative Materials - Bhagat, Tushar Vitthalrao; Gupta, Vyankatesh; Nagpal, Ravi; Heda, Anant; Khandelwal, Akansha; Alokla, Mohammad; AlGhannam, Shahad Saleh; Gowdar, Inderjit Murugendrappa; Zaman, Mahmud Uz (Bangladesh Journal of Medical Science, 2026)
Background As dental disease remains a significant concern in many developing countries, the durability and quality of these restorations are of utmost importance. Their longevity and clinical success depend primarily on the properties of dental materials and on the proper selection of these materials for restorations. Although the past few decades have revolutionised restorative dentistry through advanced materials, nanotechnology, and digital techniques, unpredictability between laboratory results and clinical outcomes persists in some cases. This narrative review will synthesize current evidence to demonstrate how the physical, chemical, and biological properties of materials influence their durability and the patient’s comfort. Methods A structured narrative literature review was conducted. Peer-reviewed articles were identified through PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar, covering January 2019 to October 2025. Search terms included combinations of “dental restorative materials,” “mechanical properties,” “clinical performance,” “testing,” and “biocompatibility.” Only English-language studies focusing on restorative materials’ properties, testing–performance correlation, and selection criteria were included. Studies unrelated to restorative applications, grey literature, and non-peer-reviewed reports were excluded. Results: ninetynine recent studies met the inclusion criteria. Recent composites, ceramics, and hybrid materials showed significant improvements in flexural strength, wear resistance, and esthetic performance; however, chemical stability and hydrolytic degradation remain limiting factors. Bioactive and “smart” materials with ion release, antibacterial agents, and pH responsiveness demonstrated enhanced remineralization potential but lack standardized long-term validation. Digital workflows (CAD/CAM and 3D printing) increased customisation and precision, but need further optimisation of post-curing and fatigue performance. Overall, differences between in-vitro testing and in-vivo longevity still exist due to variations in test design and oral simulation parameters. Conclusions: Selection of materials in restorative dentistry must be based on a comprehensive understanding of mechanical, chemical, and biological behaviours under oral conditions. Future research should emphasise standardised testing, long-term clinical trials, and the integration of bioactive materials and AI-assisted design approaches to improve material predictability and the longevity of restorations. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S78-S88